2011
DOI: 10.1159/000330199
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel plus Oxaliplatin in Combination with Capecitabine as First-Line Treatment for Advanced Gastric Cancer

Abstract: Objective: In the present phase II study, we evaluated the efficacy and safety of a docetaxel-oxaliplatin-capecitabine combination as a first-line treatment in patients with advanced gastric cancer. Patients and Methods: A total of 27 patients (18 males) with histologically confirmed inoperable gastric adenocarcinoma were recruited. Docetaxel was given (50 mg/m2 i.v.) on day 1 followed by oxaliplatin (75 mg/m2 i.v.) also on day 1. Capecitabine (2,750 mg/m2) was given orally as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 48 publications
1
8
1
Order By: Relevance
“…The median OS and PFS times of 11.3 and 6.2 months in patients with good risk TSER genotypes were also comparable to those reported in non-genotype selected populations (Figure 2). Although the observed response rate did not support the utility of TSER genotyping as a treatment selection guide, it should also be noted that the enrolled patients experienced a very promising disease control rate of 95.7% (9 PR and 13 SD out of 23 patients), higher than those reported in the literature [32][36]. The high disease control rate in the current study may provide the first prospectively obtained evidence for the utility of TSER genotyping in improving clinical outcomes in patients with gastric and GEJ cancers.…”
Section: Discussioncontrasting
confidence: 68%
“…The median OS and PFS times of 11.3 and 6.2 months in patients with good risk TSER genotypes were also comparable to those reported in non-genotype selected populations (Figure 2). Although the observed response rate did not support the utility of TSER genotyping as a treatment selection guide, it should also be noted that the enrolled patients experienced a very promising disease control rate of 95.7% (9 PR and 13 SD out of 23 patients), higher than those reported in the literature [32][36]. The high disease control rate in the current study may provide the first prospectively obtained evidence for the utility of TSER genotyping in improving clinical outcomes in patients with gastric and GEJ cancers.…”
Section: Discussioncontrasting
confidence: 68%
“…In Japan, gastric cancer is one of the most common causes of mortality, despite advances in diagnosis and treatment. In particular, unresectable or recurrent gastric cancer is associated with extremely poor prognosis even when treated with novel therapeutic agents, including taxanes [paclitaxel (2,3) and docetaxel (4,5)], irinotecan (6,7), oxaliplatin (8,9), S-1 (10), and capecitabine (11), which are known to be efficacious in gastric cancer. A multi-center randomized controlled trial (SPIRITS trial) performed in Japan reported that the median overall survival (OS) and progression-free survival in patients with advanced gastric cancer treated with S-1 plus cisplatin were significantly longer in those treated with S-1 alone (10).…”
Section: Introductionmentioning
confidence: 99%
“…A 3-week DOX regimen consisting of docetaxel at 60 mg/m 2 and oxaliplatin at 100 mg/ m 2 on day 1 and continuous orally administered capecitabine at 1000 mg/m 2 daily yielded an ORR of 52.1 %, a median PFS of 6.9 months, and a median OS of 12.6 months [18]. When docetaxel at 50 mg/m 2 and oxaliplatin at 75 mg/m 2 were administered intravenously on day 1, and capecitabine at 2750 mg/m 2 was administered orally on days 1-7 every 2 weeks, the ORR, median TTP, and median OS were 59 %, 10.0 months, and 18.0 months, respectively [19]. Considering also our study, docetaxelcontaining triplet regimens demonstrated better treatment outcomes compared with those for doublets including platinum and fluoropyrimidine.…”
Section: Discussionmentioning
confidence: 99%